Photochemistry and radiation chemistry: Complementary methods for the study of electron transfer - Wishart, James F (American Chemical Society, 2014)
This text stresses the interplay between radiation chemistry and photochemistry in studies of electron transfer. It aims to update methods and applications, collecting work from experts in the fields of chemistry, biology and materials. A summary of uses of radiation techniques is provided.